Tata Kelola Teknologi Informasi Dengan Kerangka Kerja COBIT 5 Pada Lembaga Pemerintah Dan Swasta - Putra, Ida Bagus Agung Eka Mandala; Gunantara, Nyoman; Sudarma, Made (Majalah Ilmiah Teknologi Elektro, 2021)
Information technology governance is an integral component of organizational control that includes organizational structure, information technology, and business strategies within the organization. Information technology governance is oriented in emphasizing the use of information technology in organizations to be useful and able to contribute to achieving organizational goals. To know the application of information technology governance, it is said to be good, it is necessary to assess to determine the ability of information technology governance in aligning business strategies with information technology processes. COBIT 5 is a comprehensive framework and can help (governance) management and (management) management in obtaining the goals of the organization/company. This study aims to determine the application of the COBIT 5 framework to measure the maturity level of information technology governance in institutions or organizations in Indonesia. It was found that COBIT 5 has been applied to various types of organizations such as private companies, government agencies, hospital agencies, and educational institutions. The average government and health institutions expect to achieve capability level 5 to get the optimal process, while the average achievement level capability is at level 3 with a value of 2. Therefore, it is necessary to provide recommendations for improvement to achieve expectations at capability level 5. Therefore, the purpose of this study is to review research related to the application of COBIT 5 in measuring the maturity level of information technology governance in companies, government agencies, hospitals, and educational institutions.